Pengaruh Pelaporan Keberlanjutan terhadap Biaya Modal dengan Kecakapan Manajerial sebagai Variabel Moderasi - Fitriani; Rizky Ridwan; Amalia Siti Khodijah (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to comprehensively examine the impact of sustainability reporting on capital costs through a multidimensional approach and managerial skills as moderation. Method: This study uses a quantitative method with multiple linear regression and moderated regression analysis (MRA) in non-financial companies on the IDX in 2023-2024 by using purposive sampling in the sample selection process to suit the research objectives. Finding: The results of the study show that sustainability reporting in full or per dimension, namely economic, environmental and social, does not have a significant effect on capital costs. The moderation test found managerial proficiency only strengthened the positive relationship between the environmental dimension and the cost of capital. Novelty: This study offers a new contribution to the literature on the influence of sustainability reporting on capital costs and considers managerial skills as a moderation variable by separating the three components of disclosure in sustainability reporting, namely economic, environmental, and social.